Assessment of clinical VIDA score, lesional and perilesional dermoscopy to evaluate stability of the disease in vitiligo - Smrutirama Maloji Ramawanshi; Manisha Chandela; Divya Manjegowda; Smriti Kumar; Swaraj Potdar (Wolters Kluwer Medknow Publications, 2024)
Introduction: Vitiligo is a complex dermatosis with an uncertain etiology, variable clinical presentations, an unpredictable course and prognosis, and difficult to treat. Surgical intervention is recommended for patients with a stable, nonprogressive vitiligo. Dermoscopy can detect the subtle changes in the pigmentary pattern and aid in the diagnosis of evolving lesions. This study was undertaken to measure the stability of the disease by classifying the patients as clinically stable and active and observing dermatological parameters. Objective: The aim of the study is to evaluate assess the correlation between the clinical and dermoscopic features in stable and active cases of vitiligo. Materials and Methods: Forty patients of vitiligo. Clinical VIDA score and six lesional and perilesional dermoscopic parameters were analyzed. Statistical analysis was done to determine their correlation. Results: Altered pigment network (91.6%) was the most observed dermoscopic feature followed by perifollicular depigmentation (66.7%) in clinically unstable patients and altered pigment network (87.5%) followed by leucotrichia (68.8%) was seen in clinically stable patients. However, vascularity and Koebner's phenomena failed to produce the same. Conclusion: Lesional and perilesional dermoscopic examination together for the above four parameters (pigmentary network, perifollicular changes, perilesional hypopigmentary macules, and leucotrichia) will produce reliable diagnostic approach for differentiating patients as clinically stable or unstable along with clinical VIDA score.